GSTM1 and Liver Iron Content in Children with Sickle Cell Anemia and Iron Overload - Puri, Latika (J Clin Med, 2019)
Chronic blood transfusions in patients with sickle cell anemia (SCA) cause iron overload, which occurs with a degree of interpatient variability in serum ferritin and liver iron content (LIC). Reasons for this variability are unclear and may be influenced by genes that regulate iron metabolism. We evaluated the association of the copy number of the glutathione S-transferase M1 (GSTM1) gene and degree of iron overload among patients with SCA. We compared LIC in 38 children with SCA and ≥12 lifetime erythrocyte transfusions stratified by GSTM1 genotype. Baseline LIC was measured using magnetic resonance imaging (MRI), R2*MRI within 3 months prior to, and again after, starting iron unloading therapy. After controlling for weight-corrected transfusion burden (mL/kg) and splenectomy, mean pre-chelation LIC (mg/g dry liver dry weight) was similar in all groups: GSTM1 wild-type (WT) (11.45, SD±6.8), heterozygous (8.2, SD±4.52), and homozygous GSTM1 deletion (GSTM1-null; 7.8, SD±6.9, p = 0.09). However, after >12 months of chelation, GSTM1-null genotype subjects had the least decrease in LIC compared to non-null genotype subjects (mean LIC change for GSTM1-null = 0.1 (SD±3.3); versus −0.3 (SD±3.0) and −1.9 (SD±4.9) mg/g liver dry weight for heterozygous and WT, respectively, p = 0.047). GSTM1 homozygous deletion may prevent effective chelation in children with SCA and iron overload.